(untitled) (African Journal of Biomedical Research, 2020)
Community pharmacists are readily accessible to patients for counselling services on their disease state, medications and medical devices. Previous studies have reported asthma patients’ poor inhaler techniques. This study evaluated community pharmacists’ competence for educating asthmatic patients on the use of asthma devices. The cross-sectional study was conducted with community pharmacists in Enugu State, Nigeria (May 2017 – July 2017). A 29-item structured self-administered questionnaire assessing information on stock, action plan for pharmacists, interventions with asthma patients and factors influencing these interventions was utilized. Validated checklists assessed inhaler techniques and peak flow meter use, from participants’ demonstrations. Dummy inhalers and peak flow meters were used to teach correct techniques. Of the 116 registered community pharmacists, 62 completed and returned their questionnaires (53.4% participation rate). More than half of the participants were less than 40 years old (63%), male (71.0%), had community pharmacy experience less than 10 years (67.7%). Few of the community pharmacists (3.2%) stocked spacers or peak flow meters. More than half (71%) of the participants claimed to educate patients on correct inhaler techniques but a quarter (24.2%) agreed that they lacked competence to educate on inhaler techniques. Less than half of them (46.8%) were willing to intervene with asthma patients. Summarily, the demonstrated good techniques were: pMDI (35.5%), Accuhaler (29.0%), Turbuhaler (14.5%), pMDI plus spacer (9.7%), peak flow meter (4.8%). The community pharmacists demonstrated poor inhaler techniques and were deficient in the knowledge of peak flow meter use which limited their roles in asthma management.